Wing Design for Class I Mini Unmanned Aerial Vehicles—Special Considerations for Foldable Wing Configuration at Low Reynolds Numbers - Eleftherios Karatzas; Eleftherios Nikolaou; Antonis Pitsis; Spiridon Alexopoulos; Vaios Lappas; Vassilis Kostopoulos (Engineering Proceedings)
Foldable wing designs are becoming increasingly popular due to their advantages in the rapid deployment and compact packaging of fixed-wing UAVs, particularly when compared to horizontal take-off and VTOL counterparts. However, selecting an appropriate wing design requires the careful consideration of aerodynamic performance and volume storage constraints. As a result, a trade-off between performance and practicality must be addressed during the conceptual design phase. The primary objective of this study is to identify the optimal wing configuration for a tube-launched foldable wing design. To achieve this, the analysis combine an in-house design tool developed in Excel and XFLR5 v7.01 software.